Manifestations Of Sectarian Wars In The Arab Feminist Novel, The Novel A Light Pink Dream Is An Arabic Model - salmi, asma; ameur, Ridha (El Omda in Linguistics and Discourse Analysis, 2024)
Abstract : Many Arab feminist novels have shed light on sectarian wars and their repercussions in Iraq, sparking political and cultural controversies. The narrative imagination has been a crucial and effective tool in providing different interpretations and exploring the dimensions of this issue, the novel "A Pale Pink Dream" by the Iraqi writer Maissalon Hadi provides a fertile ground for study, the novelist has sought to portray the war led by the United States on Iraq and the internal conflicts and fractures it left within Arab identity, using a narrative language with a calm pace. Therefore, the research problem is based on how the narrative produces representations of sectarian wars with their complexities, moving beyond mere reporting, instead, it takes on a character of questioning the cultural and human reality to create an alternative reality that attempts to sift through human values and find a voice opposing violence.